Controlling reaction pathways of selective C–O bond cleavage of glycerol. Issue 1 (December 2018) - Wan, Weiming; Ammal, Salai; Lin, Zhexi; You, Kyung-Eun; Heyden, Andreas; Chen, Jingguang
Abstract The selective hydrodeoxygenation (HDO) reaction is desirable to convert glycerol into various value-added products by breaking different numbers of C–O bonds while maintaining C–C bonds. Here we combine experimental and density functional theory (DFT) results to reveal that the Cu modifier can significantly reduce the oxophilicity of the molybdenum carbide (Mo2 C) surface and change the product distribution. The Mo2 C surface is active for breaking all C–O bonds to produce propylene. As the Cu coverage increases to 0.5 monolayer (ML), the Cu/Mo2 C surface shows activity towards breaking two C–O bonds and forming ally-alcohol and propanal. As the Cu coverage further increases, the Cu/Mo2 C surface cleaves one C–O bond to form acetol. DFT calculations reveal that the Mo2 C surface, Cu-Mo interface, and Cu surface are distinct sites for the production of propylene, ally-alcohol, and acetol, respectively. This study explores the feasibility of tuning the glycerol HDO selectivity by modifying the surface oxophilicity. The hydrodeoxygenation (HDO) reaction is an important pathway to upgrade glycerol, but a fundamental explanation for the selectivity toward breaking different number and type of the CO bonds is still lacking. Here, the authors explore the possibility of tuning the HDO selectivity by manipulating the surface oxophilicity.